Renal sarcoidosis: approach to diagnosis and management - Bergner, Raoul; Löffler, Christian (Current opinion in pulmonary medicine, 2018)
Purpose of reviewThe purpose of this article is to provide understanding of renal sarcoidosis, the different types of renal sarcoidosis, disease burden of renal involvement, and treatment options. Recent findingsThe frequency of renal involvement seems to be underestimated, but renal sarcoidosis repr
Gesehen am 28.06.2019